Mental Health at the Crossroads of Policy and Practice: A Legal-Epidemiological Study of Indonesian Adolescents - Rosnalisa Zein; Iwan Kusnawirawan; Dwi Ratna Sari Handayani; Hernayati; Muhammad Arsyad Subu; Imam Waluyo (Asian Journal of Healthcare Analytics, 2026)
Adolescence is a critical period for mental health development, yet in Indonesia, systemic and legal gaps exacerbate vulnerabilities related to anxiety, depression, and self-confidence. While previous research highlights gender and school-type differences, few studies integrate a legal health perspective to frame these disparities within Indonesia’s evolving mental health and education policies. This study examines the psycho-legal implications of anxiety, depression, and self-confidence among Indonesian adolescents across gender and school types, with a focus on rights-based interventions. A cross-sectional survey was conducted with 311 high school students (167 females, 144 males; 217 public, 94 private) in North Jakarta. Participants completed the Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), and the Self-Confidence Inventory (SCI). Data were analyzed using factorial ANOVAs and multiple regression. Students from private schools reported significantly higher anxiety and lower self-confidence than those in public schools. Female adolescents had significantly lower self-confidence than males. The findings highlight the private school environment as a potential risk factor and underscore the profound impact of depressive symptoms on an adolescent's self-concept. The persistent gender gap in self-confidence, independent of anxiety and depression, points to underlying sociocultural factors. Interventions must be targeted.